A Cross-Culture Understanding of Gender Construction and Women Sexuality: Exploring Women's Sexual Autonomy and Gender Construction across Cultures (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper attempts to address the conceptual and empirical understanding of sexuality differs from one society to other society and its context. Sexual desire and autonomy is a natural right for a person. Apparently exercising of these rights in public-private sphere limited to men only. Therefore, women are not able to access their sexual freedom. However, women body is contested by religion and cultural norms, rules and regulation. Along that the practices like marriage, economic coercion, and cultural rituals abandon women’s sexual desire and which turn into the cultural policing by the orthodox protector who claims for social order. However, the central idea of this paper is to analyses the question of women sexual freedom in the society. At the level of individual, it is related to women’s choices, desire and natural right but on the state and institution level, law gives equal entitlement to both the gender. Therefore, this paper has opted for feminist perspective to see the women sexual autonomy with descriptive and comparative analysis.